2022
DOI: 10.3390/ijerph191610165
|View full text |Cite
|
Sign up to set email alerts
|

The More Natural the Window, the Healthier the Isolated People—A Pathway Analysis in Xi’an, China, during the COVID-19 Pandemic

Abstract: This study explores how windows with a green view might affect the mental health (i.e., depressive/anxiety symptoms) of home-isolated populations. An online survey was conducted among 508 adults isolated under government quarantine policies for COVID-19 emergency pandemic control between 10 and 20 January 2022 in Xi’an, China. Structural equation modeling was employed to identify the pathways from green view through windows to isolated people’s depressive/anxiety symptoms. The relative frequency of plant/water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Having a view of nature at home or in living spaces may be beneficial to mental health. Multiple studies have reported that viewing nature from the living space is positively associated with distress tolerance [ 13 ], life satisfaction [ 13 , 33 , 34 ], self-esteem [ 33 ], happiness [ 33 ], and wellbeing [ 13 ]; and inversely associated with depression [ 13 , 33 , 34 ], anxiety [ 13 , 33 , 34 ], loneliness [ 13 , 33 ], and negative affect (negative emotions) [ 35 ]. In contrast, having a limited view or no view of nature at home has been associated with experiencing depression [ 36 , 37 ] and poorer wellbeing [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a view of nature at home or in living spaces may be beneficial to mental health. Multiple studies have reported that viewing nature from the living space is positively associated with distress tolerance [ 13 ], life satisfaction [ 13 , 33 , 34 ], self-esteem [ 33 ], happiness [ 33 ], and wellbeing [ 13 ]; and inversely associated with depression [ 13 , 33 , 34 ], anxiety [ 13 , 33 , 34 ], loneliness [ 13 , 33 ], and negative affect (negative emotions) [ 35 ]. In contrast, having a limited view or no view of nature at home has been associated with experiencing depression [ 36 , 37 ] and poorer wellbeing [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, satisfaction with greenspace has been associated with positive mental health [ 47 ] and quality of life [ 48 ]. Many of the studies which presented these findings were undertaken during the COVID-19 pandemic [ 13 , 33 , 34 , 37 , 43 ], a time of greater distress and when stay-at-home measures may have been implemented. Therefore, these findings should be confirmed when the population is not in a crisis situation.…”
Section: Resultsmentioning
confidence: 99%
“…It clearly indicates a need to adapt the construction norms. In addition, even though both legislative systems fully address the MH1, the inclusion of plants and gardens indicator, many studies emphasize the importance of green spaces for mental health during pandemics (Bi et al. , 2022; García Flores and Ordoñez Díaz, 2022; Maury-Mora et al.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have underscored the heightened vulnerability of certain nomadic populations, such as the Gypsy, Roma, and Traveler (GRT) communities, to COVID-19, with increased risks of infection, mortality, and various socio-economic impacts [ 5 ]. However, the nomadic lifestyle's outdoor exposure could potentially offer health benefits, including physical activity encouragement, psychological stress relief, recovery from memory impairment and concentration problems, enhanced sense of well-being, and improved social cohesion [ 6 ].…”
Section: Introductionmentioning
confidence: 99%